Pendampingan UMKM : Pembuatan NIB, Branding, dan Digitalisasi Melalui Google Maps Di Dusun Sabatan - Maharani Dara Dinanti; Rois Nafi`udin; Dewi Maryam; Mahadewi Ratuna Hati; Raditya Hendra Mukti; Susanti Malasari (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Micro, Small and Medium Enterprises (MSMEs) play an important role in Indonesia's economic growth. However, many MSME players in Sabatan Hamlet, Ringinanom Village, Magelang Regency, do not have business legality, strong branding, and effective digital marketing strategies. This mentoring program aims to assist MSME players in obtaining a Business Identification Number (NIB), improving branding identity, and utilizing Google Maps as a means of business digitization. The methods used include observation, interviews, mentoring, and evaluation of six MSMEs in Sabatan Hamlet. The results of this program show that the assisted MSMEs have successfully obtained business legality in the form of NIB, have a more professional business logo and banner, and are registered on Google Maps, which increases the visibility of their business. The evaluation of this program also showed a positive response from MSME players, who felt the real impact of the assistance in the aspects of legality, branding, and digital marketing. With this program, it is expected that MSMEs in Sabatan Hamlet can develop more rapidly, increase competitiveness, and contribute more to the local economy. Similar programs in the future need to be expanded so that more MSMEs can benefit, with additional training related to digital marketing strategies and business management.